유류분제도의 현황과 개선방안 ―유류분의 산정을 중심으로― - 전경근 (가족법연구, 2018)
The system of legal portion of an heir was introduced by the amendment of the Civil Law in 1977. In the newly introduced system, there are four articles about the calculation of the legal portion of an heir. First, Article 1113 of the Civil Act prescribes the range of property for the calculation of the legal portion of an heir. Second, Article 1114 regulates the scope of the gift that should be included to calculate the legal portion of an heir. Third, Article 1115, which determines the property that should be returned when claiming the return of the calculated legal portion by Article 1113 and 1114, and forth, Article 1116 determines the order of the returned property. Among these, Article 1113 does not provide sufficient details on the method of calculating the amount of legal portion of an heir, so in practice, more precise calculation formulas are developed to calculate the amount of legal portion. However, the problem in operating these equations is about the gift which is to be included, regulated by Article 1114. It seems that there is no problem because of a limitation due to the period, but the aspect that there is no limitation of period regarding the gift to the heir is causing many disputes. In claiming the return of the property to the donee or inheritor for the preservation of the legal portion, the extent of the return shall be proportional to the amount of the increase in the amount of each inheritance, and this should include the testamentary gift as well as the cost of gift. Article 1116, on the other hand, secures the security of the transaction by allowing the beneficiary to first receive the return from the forfeited property remaining in the name of the heir in the case of a gift and bequest by the deceased person. However, if there is a cross between the gift and the bequest, such as the case of some people received the gift and the others received bequest, the fact that the bequest must be returned first is inconsistent with Article 1115 which regulates that the return should be proportional to the amount of increase in the amount. Therefore, in this paper, the conclusion that each heir shall return in proportion to the value of the property with special profit is suggested regarding the range of the property that should be included in calculation of the legal portion and the return of the gift and bequest. In addition, issues like the relation between the return of original object and the return of value, the way to determine the relationship between legal portion and part of contribution in returning legal portion are briefly discussed in the paper.
Keywords: 유류분; 유류분의 반환; 증여; 유증; 기여분; legal portion of an heir; return of legal portion; gift; bequest; testamentary gift; part of contribution